City of devils : the two men who ruled the underworld of old Shanghai - French, Paul, 1966- (Picador, 2018)
Shanghai, 1930s; it was a haven for outlaws from all over the world: a place where pasts could beforgotten, fascism and communism outrun, names invented, and fortunes made<U+2015>and lost. “Lucky” Jack Riley was the most notorious of those outlaws. An ex<U+2013>U.S. Navy boxing champion, he escaped from prison and rose to become the Slots King of Shanghai. “Dapper” Joe Farren<U+2015>a Jewish boy who fled Vienna<U+2019>s ghetto<U+2015>ruled the nightclubs. His chorus lines rivalled Ziegfeld<U+2019>s. In 1940, Lucky Jack and Dapper Joe bestrode the Shanghai Badlands like kings, while all around the Solitary Island was poverty, starvation, and war. They thought they ruled Shanghai, but the city had other ideas. This is the story of their rise to power, their downfall, and the trail of destruction left in their wake. Shanghai was their playground for a flickering few years, a city where for a fleeting moment even the wildest dreams could come true.